2011
DOI: 10.1121/1.3598463
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic attenuation, phase and group velocities in liquid-filled pipes II: Simulation for spallation neutron sources and planetary exploration

Abstract: This paper uses a finite element method (FEM) to compare predictions of the attenuation and sound speeds of acoustic modes in a fluid-filled pipe with those of the analytical model presented in the first paper in this series. It explains why, when the predictions of the earlier paper were compared with experimental data from a water-filled PMMA pipe, the uncertainties and agreement for attenuation data were worse than those for sound speed data. Having validated the FEM approach in this way, the versatility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The driving frequency of the function generator, which does not necessarily equal the peak frequency of the energy in the water (Baik et al 2010) was incremented from 15 to 35 kHz in 1 kHz steps, with 20 cycles per pulse. To obtain the sound speed and attenuation at each frequency, the two-dimensional Fourier Transform technique and Prony's method were adopted (Baik et al 2010;Jiang et al 2011).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The driving frequency of the function generator, which does not necessarily equal the peak frequency of the energy in the water (Baik et al 2010) was incremented from 15 to 35 kHz in 1 kHz steps, with 20 cycles per pulse. To obtain the sound speed and attenuation at each frequency, the two-dimensional Fourier Transform technique and Prony's method were adopted (Baik et al 2010;Jiang et al 2011).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This inversion is validated against simulated data from pipes and is shown to give similar levels of accuracy to those obtained when the PWFF inversion is applied to data taken in PWFF conditions. Section 3 describes experimental tests on water-filled poly methylmethacrylate (PMMA) pipes, which had previously been shown to mimic the acoustic coupling that would occur in the mercuryfilled steel pipes of ORNL's SNS TTF (Baik et al 2010;Jiang et al 2011). Although these data show that the new inversion technique would provide accurate BSDs if the frequency range of the original sensor design were to be used, budget cuts forced by the 2008 global financial crisis dramatically reduced the frequency range that could be afforded.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of bubbles in pipelines, the assumption that there exists in bubble-free conditions a single frequencyindependent sound speed and frequency-dependent attenuation (against which to compare the measurements in bubbly conditions) is flawed. This is because the liquid and pipe are acoustically coupled 20,21 and because, over most of the frequency range of interest in some pipe systems (such as SNS), modal acoustic propagation occurs with distinct frequencydependent sound speeds and attenuations for each mode. The current authors 10 showed that errors of þ/À 1000% can occur when such an approach is followed in a pipe of similar dimension to that used in the SNS at Oak Ridge National Laboratory (ORNL).…”
Section: Introductionmentioning
confidence: 99%
“…These included investigating the lakes and methanefall soundscapes of Titan, 30,31 and probing the ice seas of Europa [32][33][34] or atmospheric fluctuations in Venus. 35 They included looking at the way the extreme density contrasts that occur in transitioning from Earth's atmosphere to those of other worlds might introduce unexpected effects or errors, if we base our mission planning on instrument performance, 36,37 calibration, or procedures 38 that are familiar from Earthbased practices. In order to design, deploy, and interpret acoustic systems for anemometry, 39 or infer atmospheric chemistry from the local sound speed, 40,41 predict the sound of thunder on Titan, 42 or for public engagement predict how voices or musical instruments might sound on other worlds, [43][44][45] we need to know the speed of sound 46,47 and absorption.…”
Section: Introductionmentioning
confidence: 99%